The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1017/s1049023x00002302
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Management of Earthquake Casualties Buried Under Rubble

Abstract: Earthquakes continue to exact a heavy toll on life, injury, and loss of property. Survival of casualties extricated from under the rubble depends upon early medical interventions by emergency teams on site. The objective of this paper is to review the pertinent literature and to analyze the information as a practical guideline for the medical management of casualties accidentally buried alive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 81 publications
0
41
0
Order By: Relevance
“…In fact, all hospitals and schools after the new standards and reinforcement withstood the Lushan Earthquake. Secondly, past observations of earthquakes indicate that rapid extrication and treatment are critical for the patients' survival in Ashkenazi et al 2005. The immediate needs of disaster victims must be met within hours of disaster impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, all hospitals and schools after the new standards and reinforcement withstood the Lushan Earthquake. Secondly, past observations of earthquakes indicate that rapid extrication and treatment are critical for the patients' survival in Ashkenazi et al 2005. The immediate needs of disaster victims must be met within hours of disaster impact.…”
Section: Discussionmentioning
confidence: 99%
“…Past observations of earthquakes indicate that rapid extrication and treatment are critical for the patients' survival in emergency settings (Ashkenazi et al 2005). The immediate needs of disaster victims must be met within hours of the disaster.…”
Section: Acceptance Of Emergency Medical Rescue Teamsmentioning
confidence: 99%
“…Past observations of earthquakes indicated that rapid extrication and treatment are critical for the patients' survival in emergency settings (Ashkenazi et al 2005). The immediate needs of disaster victims must be met within hours of disaster impact.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have determined that rapid extrication of victims trapped under rubble significantly reduces mortality in earthquakes. The victims tend to have typical injuries (e.g., crush syndrome), which require knowledge of appropriate treatment methods (Schultz et al 1996;PeekAsa et al 1998;Ashkenzai et al 2005;Ramirez and Peek-Asa 2005;Macintyre et al 2006;Bartal et al 2011). Therefore, the existence and efficacy of search and rescue teams combined with access to pre-hospital care may have a crucial effect on the number casualties (Haojun et al 2011).…”
Section: Medical Preparedness and Earthquake-induced Injury And Mortamentioning
confidence: 99%